ANCA-Associated Vasculitis after Moderna COVID-19 Vaccination - Shiko Gen; Takanori Iwai; Sayuri Ohnari; Kanako Nobe; Naofumi Ikeda (Case Reports in Nephrology)
We experienced a case of myeloperoxidase antineutrophil cytoplasmic antibody (MPO-ANCA)-associated vasculitis after Moderna COVID-19 vaccination. An 82-year-old woman developed pyrexia and general malaise one month after her third booster vaccine, and the symptoms persisted. Blood testing revealed inflammation, a high level of MPO-ANCA, and microscopic hematuria. MPO-ANCA-associated vasculitis was diagnosed by renal biopsy. The symptoms improved with steroid therapy. Common adverse reactions to mRNA vaccines against COVID-19 include pyrexia and general malaise, but MPO-ANCA-associated vasculitis can also occur. If pyrexia, prolonged general malaise, urinary occult blood, or renal impairment is observed, the onset of MPO-ANCA-associated vasculitis should be considered.